Financial Deepening, Property Rights and Poverty : Evidence From Sub-Saharan Africa - Huang, Yifei (IMF Working Papers; Working Paper ;, 2011)
Recent studies on the relationship between financial development and poverty have been inconclusive. Some claim that, by allowing more entrepreneurs to obtain financing, financial development improves the allocation of capital, which has a particularly large impact on the poor. Others argue that it is primarily the rich and politically connected who benefit from improvements in the financial system. This paper looks at a sample of 37 countries in sub-Saharan Africa from 1992 through 2006. Its results suggest that financial deepening could narrow income inequality and reduce poverty, and that stronger property rights reinforce these effects. Interest rate and lending liberalization alone could, however, be detrimental to the poor if not accompanied by institutional reforms, in particular stronger property rights and wider access to creditor information.